Latest Pleistocene to Holocene Thrusting Recorded by a Flight of Strath Terraces in the Eastern Qilian Shan, NE Tibetan Plateau. Issue 12 (13th December 2017) - Xiong, Jianguo; Li, Youli; Zhong, Yuezhi; Lu, Honghua; Lei, Jinghao; Xin, Weilin; Wang, Libo; Hu, Xiu; Zhang, Peizhen
Abstract: At the eastern Qilian Shan mountain front in the NE Tibetan Plateau, the Minle‐Damaying Fault (MDF), the southernmost fault of the North Frontal Thrust (NFT) system, has previously been proposed as an inactive structure during the Holocene. Here we present a detailed record of six strath terraces of the Xie River that document the history of active deformation of the MDF. One optically stimulated luminescence dating sample constrains abandonment of the highest terrace T6 at 12.7 ± 1.4 ka. The formation ages of the lower terraces (T4 –T1 ) are dated by AMS 14 C dating. The cumulative vertical offsets of the MDF recorded by these terraces are determined as 12.2 ± 0.4 m (T6 ), 8.0 ± 0.4 m (T5 ), 6.4 ± 0.4 m (T4 ), 4.6 ± 0.1 m (T3 ), and 3.2 ± 0.2 m (T1c ) by an unmanned aerial vehicle system, respectively. A long‐term vertical slip rate of the MDF of 0.9 ± 0.2 mm/yr is then estimated from the above data of terrace age and vertical offset by a linear regression. Assuming that the fault dip of 35 ± 5° measured at the surface is representative for the depth‐averaged fault dip, horizontal shortening rates of 0.83–1.91 mm/yr are inferred for the MDF. Our new data show that the proximal fault (the MDF) of the NFT system at the eastern Qilian Shan mountain front has remained active when the deformation propagated basinward, a different scenario from that observed at both the western and central Qilian Shan mountain front. Key Points: Deformed terraces document recent activity of the Minle‐Damaying Fault, a structure previously proposed to be inactive during the Holocene Vertical slip rates of the fault averaged over the last 12.7 kyr are on the order of 1 mm/yr Distribution of active deformation across the eastern Qilian Shan foreland is different to the western and central foreland